Glucose experiment on Picea glauca at the Agashashok River, Alaska 2019 - Patrick Sullivan; Michael Weintraub (Arctic Data Center, 2020)
Overview: It has long been thought that temperature exerts a direct control on growth of treeline trees and the position of the treeline. However, our recent work in the Arctic with white spruce suggests that indirect effects of temperature on soil nutrient availability may be of equal or greater importance. We hypothesize that cold soils at the treeline, particularly during winter, limit microbial activity and nutrient availability to the point where trees are barely able to survive and grow. Measurements made during winter have revealed that Arctic forests maintain snowpacks that are much deeper than observed at treeline. Trees are thought to trap snow and lead to a deeper snowpack, insulating the soil from cold air and allowing for greater overwinter microbial activity and greater nutrient mineralization. Indeed, we found a strong positive correlation between white spruce growth and winter snow depth. We propose to isolate the mechanisms underlying this correlation by using snowfences to manipulate winter snow depth and fertilizer to increase soil nutrient availability at three treelines that differ in soil moisture. To provide an experimental test of the importance of temperature as a direct control on treeline tree growth, we propose to incorporate experimental shoot warming into our snowfence experiment in a factorial design. We predict that both experimental snow and nutrient additions will lead to large increases in microbial activity, photosynthesis, tree growth, seed quality, seed production, seedling establishment and recruitment of new trees. We expect to observe the greatest positive responses where soils are wet and cold. Meanwhile, we predict that shoot warming will lead to negligible changes in growth. This research will elucidate the relationship between snow depth and soil nutrient availability, and determine the relative importance of nutrient and temperature limitations at treeline to white spruce – a dominant member of the boreal forest and the northernmost tree species in North America. Intellectual Merit: The position of the Arctic treeline is an important regulator of surface energy budgets, carbon cycling and subsistence resources in high latitude environments. Our recent research provides correlative evidence of the importance of winter snow depth as a driver of tree growth. Here, we propose to experimentally isolate the importance of snow depth and soil nutrient availability and examine the consequences for microbial processes and tree performance. This is a novel proposal, as we aim to link microbial ecology with large-scale landscape patterns of relevance to regional and global climates. If our hypotheses are confirmed, our findings will contradict the prevailing theory of treeline causation, alter our predictions of where and when treelines may advance and necessitate revision of the many paleoclimate reconstructions based upon correlations between temperature and tree growth near the Arctic treeline.